ANALISIS KEBUTUHAN TENAGA PERAWAT POLIKLINIK DAN TENAGA TPPRJ BERDASARKAN INDIKATOR PELAYANAN RAWAT JALAN DENGAN JUMLAH KUNJUNGAN DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU PERIODE TRIWULAN TAHUN 2015 - Daniati, Sy. Effi (Sistem Informasi, 2017)
Rsud arifin achmad riau 17 service polyclinic by the number of nurse 75 people and numbers of workers tpprj as many as 8 people.Research objectives perceive the percentage visits outpatient.Research methodology deskriftif with the kind of research evaluation.The results of the study obtained visits per day 732 patients with the number of officials tpprj 8 people, visits new per day 113 with the number of officials as many as 2 people, the ratio new visits with a total visit as many as 15: 100 patients per day, the percentage service unit outpatient the visit is highest in the polyclinic a disease in with the lowest in the polyclinic psychology with numbers of workers nurse 75 power nurses and the ratio visits with exertion nurse as many as one nurses serving 11 patients.Need to evaluation with numbers of workers should 11 officers, on the ground in find there are six officer as need to the addition of 5 officers registration patients long to produce officers working optimal.